Role of the Gut Microbiota in Children with Kidney Disease - You-Lin Tain; Chien-Ning Hsu (MDPI AG, 2023)
Disruption of the composition and structure of the gut microbiota, namely dysbiosis, dictates the pathophysiology of kidney diseases. The bidirectional kidney-gut axis is of interest in chronic kidney disease (CKD); the uremic milieu leads to intestinal dysbiosis and gut microbial metabolites and toxins implicated in the loss of kidney function and increased comorbidity burden. Considering that kidney diseases can originate in childhood or even earlier in fetal life, identification of the pathogenetic connection between gut microbiota dysbiosis and the development of pediatric renal diseases deserves more attention. This review concentrates on the pathogenic link between dysbiotic gut microbiota and pediatric renal diseases, covering CKD, kidney transplantation, hemodialysis and peritoneal dialysis, and idiopathic nephrotic syndrome. Gut microbiota-targeted therapies including dietary intervention, probiotics, prebiotics, postbiotics and fecal microbial transplantation are discussed for their potential for the treatment of pediatric renal diseases. A deeper understanding of gut microbiota in pediatric renal diseases will aid in developing innovative gut microbiota-targeted interventions for preventing or attenuating the global burden of kidney diseases.